Effects of calving and submarine melting on steady states and stability of buttressed marine ice sheets - Haseloff, Marianne; Sergienko, Olga V. (Journal of Glaciology, 2022)
Mass loss from ice shelves is a strong control on grounding-line dynamics. Here we investigate how calving and submarine melt parameterizations affect steady-state grounding-line positions and their stability. Our results indicate that different calving laws with the same melt parameterization result in more diverse steady-state ice-sheet configurations than different melt parameterizations with the same calving law. We show that the backstress at the grounding line depends on the integrated ice-shelf mass flux. Consequently, ice shelves are most sensitive to high melt rates in the vicinity of their grounding lines. For the same shelf-averaged melt rates, different melt parameterizations can lead to very different ice-shelf configurations and grounding-line positions. If the melt rate depends on the slope of the ice-shelf draft, then the positive feedback between increased melting and steepening of the slope can lead to singular melt rates at the ice-shelf front, producing an apparent lower limit of the shelf front thickness as the ice thickness vanishes over a small boundary layer. Our results illustrate that the evolution of marine ice sheets is highly dependent on ice-shelf mass loss mechanisms, and that existing parameterizations can lead to a wide range of modelled grounding-line behaviours.